An Analysis of Indonesian Slang Words in Mojok Essay - Martuah Purba , Agi Julianto; Herman; Neni Purba, Christian (European Exploratory Scientific Journal, 2019)
The purpose of this study was to determine the type of use of slang language, how to form slang languages and to find out factors that influence the development of slang in Stigma Terhadap Ibu Rumah Tangga Yang Sudah Keseringan Salah Kaprah Mojok Online Essay by Dinda Asrining Tyas. Theories used in this research were I. Plag and B. Spolsky. The method used in this study was qualitative descriptive. Data were analyzed based on word formation theory by I. Plag, and W. O’Grady and V. Guzman. The results show there were several words formed through the word formation process, namely: found 2 words classified in affixation, 6 words classified in clipping, 2 words belonging to the blending and 2 compound word used by the characters in the essay. And the type of slang that is often used by Indonesians in the story is clipping. In short, this research shows that there are many aspects of slang that can be analyzed more deeply to improve our new knowledge and vocabulary.